Chemical characterization of a new carbohydrate metabolite in the vitreous of Black Moor goldfish by liquid chromatography-electrospray mass spectrometry and nuclear magnetic resonance. Issue 4 (2003) - Zhou Zhou, Lei Lei; Juneau Juneau, Gary Gary; Xiong Xiong, Xiang Xiang; Lai Lai, Helen W. L. Helen W. L.; Yew Yew, David T. David T.; Lam Lam, Kwok-Wai Kwok-Wai
Abstract : Our recent report has described the occurrence of a remarkably high amount of an unknown compound with light absorption maximum at 290 nm in the aqueous humor of Black Moor goldfish. The absorption maximum is shifted to 270 nm in 0.01% trifluroacetic acid. The concentration of this compound was very low in the eye of common goldfish and was absent in ocular fluids or serum of mammalian species. This compound was isolated by chromatography on a carbohydrate column eluted by 10 mM ammonium phosphate followed by chromatography on a Delta PAK C18 column eluted by acetonitrile–water–trifluoroacetic acid. The ion size of the unknown compound determined by electrospray for protonated and deprotonated ions are m/z 205 and 203, respectively. The protonated ion was fragmented to m/z 187, 169, 157 and 141 as the cone voltage increased. The data from mass spectrometry and nuclear magnetic resonance spectroscopy indicate the chemical structure of a carbohydrate with 7 carbons containing a lactone ring.